Occupational health and safety activities of Port Elizabeth's integrated Department of Labour Inspectorate in 2005 - Huna, Bulelwa Daniswa Denise (My University, 2010)
This study was aimed at describing the nature of Occupational Health and Safety (OHS) inspections and blitzes conducted in the Port Elizabeth Integrated Department of Labour (DoL) in 2005, the nature and number of prohibitions, contraventions, as well as improvement notices issued. The objectives were to determine the number of OHS inspections conducted in the Port Elizabeth Labour Centre (PELC) in 2005; to describe the nature of the inspections and the type of industries inspected in the PELC in 2005; and to determine the frequency and nature of prohibitions, contraventions and improvement notices issued. The data was obtained from the PELC. The results of the study revealed that the inspectorate conducted a total of 1258 and this exceeded the target of 800 OHS inspections for the PELC. However, it is questionable how this target was developed. The target is not representative and does not give an overall picture of conditions in the workplace. The results indicated that inspectors were not competent in conducting boiler inspections as well on Major Hazardous Installation (MHI) since none of these inspections were conducted. On the inception of the OHS task team, there was a sudden increase in inspections conducted in the construction industry in October 2005 as well as the rate of finalisation of incidents in November 2005 and this was attributed to the fact that they were not conducting inspections on other labour laws and were only focusing on OHS. An assessment of the inspectors’ inspection checklists revealed that the inspections were being reduced to just a yes or no tick exercise, with no recommendation on appropriate action to be taken by the employer. It became evident that the inception of a special team in September 2005 contributed to an increased number of OHS inspections, since they were only focusing on OHS issues. This team ensured that in November 2005 there were 43 incidents finalised as compared to the 101 finalised over 11 months. They also ensured that a total of 258 OHS inspections were conducted from September 2005 to December 2005. Although these inspectors were not fully competent in addressing health and s afety issues their momentary focus on OHS activities ensured that they made a difference in the rate of finalisation of incidents. However, when some of the cases were taken to court no successful prosecution could be obtained because there are no OHS focused prosecutors, which have a clear understanding of Act. Discussions with the inspectors revealed that there was a lack of morale and loss of interest in their work, thus causing them not to put in much effort. These discussions revealed that this lack of morale was caused by the frustrations they often experienced in the execution of their duties due to lack of training as well as lack of cooperation from the employers. Furthermore, the inspectors revealed that the great number of resignations from inspectors who were leaving for greener pastures left them with a lot of work with no financial incentive. It also became apparent that there was no objective strategy underlying the number of inspections required relative to the purpose of the inspections, taking into account the nature and complexity of the industry that is to be inspected. The failure of the Service Delivery Unit to give a direction on how qualitative inspections should be measured demoralised them because the focus was only on the quantity (240 inspections per annum) of inspections that are to be conducted by each inspector. It is recommended that training, which should include a proper career path be conducted for inspectors to improve the inspectors’ capability and to motivate them. Strong relations with the South African Police Services and the Department of Justice should be promoted to ensure effectiveness of service delivery. These relations will ensure that inspectors are readily assisted by the police when they deal with uncooperative employers. Training of prosecutors will ensure that they understand the OHSA and its implementation and therefore effectively defend cases that are taken to court. The targets set for inspections should be scientifically supported and take into account the nature and complexity of the production processes. Lastly, revision of salary packages should be looked into to ensure retention of competent staff. The above recommendations will only be effective if the Business Unit Manager and the Regional Manager address them through the National Department of Labour since their implementation will affect all inspectors.
Thesis (M.P.H.(Occupational Hygiene)), Faculty of Health Sciences,University of the Witwatersrand, 2009
Keywords: occupational health and safety; Port Elizabeth